Parental External Locus of Control in Pregnancy Is Associated with Subsequent Teacher Ratings of Negative Behavior in Primary School: Findings from a British Birth Cohort - Nowicki, Stephen; Gregory, Steven; Ellis, Genette L.; Iles-Caven, Yasmin; Golding, Jean (Frontiers in Psychology, 2018)
The purpose of the present study was to examine whether parents’ locus of control (LOC) obtained before the birth of their child predicts the child’s behavior at school in School Years 3 (ages 7-8) and 6 (ages 10-11). A modified version of the adult Nowicki-Strickland Internal-External locus of control scale (ANSIE) was completed by mothers and fathers in their own home during pregnancy. Externality was defined as a score greater than the median, and internality as equal to, or less than, the median. Outcomes were the five individual subscales and the total difficulties of Goodman’s Strengths and Difficulties Questionnaire completed by the children’s class teachers at the end of School Years 3 and 6. As predicted it was found that the greater the presence of externality in the parents the greater the increased risk of the child’s adverse behavior as rated by teachers. The risk was generally greatest if both parents were external and lowest if both were internal. There was a consistent relationship at both Year 3 and Year 6 between maternal externality in pregnancy and children’s emotional difficulties. However, for other behaviors the pattern of associations varied depending on whether the mother or father was external, the type of adverse behavior, and the School Year in which children were assessed. Prenatal parental externality appears to be significantly associated with a variety of children’s negative behaviors. Of note was the finding that fathers’ as well as mothers’ locus of control were important in determining children’s outcomes. Implications of the complexity of the results for the role parents may play in children’s personality and adjustment are discussed.